OP0001 Work Disability After Initiation of Anti-TNF and DMARD Treatment in Psoriatic Arthritis; Investigator LED, UK, Multicentre Observational Cohort Study (LOPAS II). (9th June 2015) - Tillett, W.; Shaddick, G.; Jobling, A.; Thomas, M.; Korendowych, E.; McHugh, N.
Abstract : Background: Work disability (WD) in Psoriatic Arthritis (PsA) is high with unemployment reported at 20-50% and presenteeism (reduced effectiveness at work) at 16-39%. We have previously reported that presenteeism is primarily associated with measures of disease activity whereas unemployment, considered the endpoint of work disability, is associated with employer factors, age and disease duration. Randomised trials have established the effectiveness of biologic agents on presenteeism in PsA. The effect of DMARD or anti-TNF treatment in a real world population has not been studied. Objectives: To investigate work disability (presenteeism and productivity loss) after commencement of standard clinical treatment (anti-TNF and DMARD) in a real life cohort of patients with PsA. Methods: Four hundred patients fulfilling CASPAR criteria for PsA were recruited from 23 hospitals across the UK. Demographic, socioeconomic, work and clinical data were collected at baseline prior to commencement of anti-TNF or DMARD. Follow up was scheduled for 2, 4, 12 and 24 weeks as part of routine practice. WD was assessed with the Work Productivity and Activity Questionnaire (WPAI-SHP) and disease activity with the DAPSA composite measure. Analysis was on intention to treat. Differences within and between groups were assessed using the Mann-Whitney U test and by calculating nonparametric 95% confidence intervals for differences using bootstrapping. Results: Two hundred and thirty six participants of any age were in work. Unemployed patients were older, 59yrs (IQR 47.7-67.8) vs 49yrs (IQR 41.7-58.0) and had worse physical function (HAQ) 1.4 (IQR 0.75-1.94) vs 1.0 (IQR 0.50-0.86) but other demographic and clinical measures were not significantly different. Patients commenced on anti-TNF had longer disease duration 11yrs (IQR 3.5-18.5) vs 5yrs (IQR 2-11) and higher tender, 16 (IQR 11-25) vs 11 (IQR 5-20.25) and swollen 7 (IQR 5-12) vs 5 (IQR 2-10) joint counts but other demographic and clinical measures were not significantly different. Amongst those commencing anti-TNF presenteeism improved from 40% (IQR 20-60) to 10% (IQR 0-30) (p0.001) and productivity loss from 45% (IQR 26.2-67-8) to 10% (IQR 0-30.0) (p0.001). Amongst those commencing DMARD presenteeism improved from 30% (IQR10-60) to 20% (IQR10-50) p=0.001 and productivity loss from 40% (IQR 20-70) to 25 (IQR 10-60) (p0.001). The difference in change of presenteeism between groups became significant at 2 weeks and was sustained to 24 weeks (figure 1 ). There were no significant changes in employment level in either treatment group. DAPSA improved over 24 weeks from 53 (IQR 38.3-68.4) to 14 (6.9-37.4) in the anti-TNF group (p0.001), defined as a good response using established cut points vs 39 (IQR 27.9-58.4) to 30 (IQR 18.4-38.5) in the DMARD group (p0.001) defined as a poor response. Conclusions: We observed a clinically significant improvement in presenteeism, productivity loss and disease activity after initiation of DMARD and anti-TNF treatment. Improvement in WD and disease activity was greater and more rapid amongst those commenced on anti-TNF. This study suggests WD is reversible in the real world setting. Disclosure of Interest: W. Tillett Grant/research support from: Abbvie laboratories ltd, G. Shaddick: None declared, A. Jobling: None declared, M. Thomas: None declared, E. Korendowych: None declared, N. McHugh: None declared